The relationship between Internet use and loneliness of middle-aged and older adult people: the moderating effect of residence - Li, Qiusha; Yang, Chunxiao; Zhao, Zixuan; Yang, Chenxiao; Chen, Zhongming; Huang, Dongmei; Yin, Wenqiang (Frontiers in Public Health, 2024)
The proportion of middle-aged and elderly people exposed to the Internet continues to grow. Internet use may have an impact on the mental health of the elderly, especially loneliness. This study analyzed the relationship between Internet use and presence of loneliness. Methods: A total of 550 person aged 45 years and above were randomly selected from a province in eastern China at the end of 2022. The outcome variable was presence of loneliness, as measured by self-report. Descriptive analysis, chi-square test and binary logistic analysis were used to analyze the data. Results: 58.3% of respondents use the Internet. Internet use could reduce the possible of reported loneliness in middle-aged and elderly people (OR=0.652, 95%CI: 0.465, 0.940), and residence played a moderating role in the relationship between them. Middle-aged and older adults who used the Internet for 1-3 hours (OR=0.464, 95%CI: 0.275, 0.784) and 3-5 hours (OR=0.484, 95%CI: 0.247, 0.946) were less likely to felt lonely than those who used the Internet for less than 1 hour per day. In addition, middle-aged and elderly people using the Internet to contact relatives and friends (OR=0.488, 95%CI:0.292, 0.818), read the news (OR=0.485, 95%CI:0.277, 0.848), assets management (OR=0.297, 95%CI:0.109, 0.818) were less likely to report loneliness, while those who made online payment (OR=3.101, 95%CI:1.413, 6.807) were more likely to report loneliness. Conclusions: There is a significant negative correlation between Internet use and presence of loneliness, but different Internet duration and content have different effects on loneliness in middle-aged and elderly people. We should pay attention to the impact of Internet use on loneliness in middle-aged and elderly people.